Purchase Intention towards IoT Smart Homes in Malaysia:A Value- Based Adoption Model - TEO, POH-CHUIN; HO, THERESA C.F.; TIE, DANIEL; HASHIM, ZAIFUL HASMI BIN MOHD (The journal of contemporary issues in business and government, 2021)
Internet of Things (IoT) has been the attention in the field of study of innovation. However, there is still lack of study in marketing, especially in the Southeast Asia context. This study strives to examine Internet of Things, specifically focused on Smart Homes in Malaysia context. Hence, this study tested the impact of antecedents and consequences of perceived value, supported by Value-Based Adoption Model (VAM). This study examines the conceptual framework using an online self-administered survey using 163 respondents and employed Smart PLS in analysing the data. The results of analysis showed that perceived fee is an important determinant for perceived value, and perceived value showed a significant positive impact on purchase intention towards Smart Homes. This study found perceived usefulness has been a significant predictor of perceived value; while perceived value showed significant positive impact on adoption intention.